No longer at ease: How digital organizational followers in Kenya are challenging contemporary leadership - Harry Kipkemoi Bett; Betty Wangui Ngala; Timothy Mwangi Kiruhi (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
The high internet penetration as well as the increasing digital platforms in Kenya has led to the transformation of many organizations in Kenya. Further, organizational followers are adopting digital technologies, and leveraging on digital platforms while working within organizations. Due to digitization, organizational followers are now collaborating, working flexibly (i.e. from home and other contexts away from work) and sharing content with people in different geographical locations. Consequently, many followers are influencing their organizational leaders. The digital transformation in the country, and among workers, suggest that organizational leaders should develop effective workable strategies and ensure they have conducive cultures that are in tandem with the digital transformation in place. This paper, based on Social Impact Theory (SIT) focuses on digitized organizational followers and their effect on firm leaders within Kenya.
Keywords: 330; Digitization; Social impact theory; Followers; Leaders; Kenya